Braquiópodos - Martínez Chacon, M.L.; Legrand-Blain, M. (Coloquios de Paleontología, 1992)
Brachiopods are locatly abundant in Los Santos de Maimona basin, where they oceur mainly in marly layers of units 1,4, and 6. The most remarkable feature of the Brachiopod -asseniblages in unU lis the abundance ofGígantoproductíds. Tlicy sbowclosc íelatioíiships with those of the Upper Viséan of central aud western Europe. Unít 3 contain sorne brachiopods with spines, bat they are very difficult t. take out of the rock, and <mly sume silicified young spccimens and microbrachiopods were coflected. Brachiopods are íess ahundant in units 4 ant] 6, but asemblages are richer. Thirty species have been idcntified in unit 6, but most of them are represented by Iess than tive specirnens. ile whole asse-mblage, composed of 44 species, shows high similarity te thebrachiopods of the Upper Viséan from western Europe, mainly of the Upper Vis¿an from Lower Silesia. Relationships are also notable to the Moscow Basin, Donetz, Fergana, North Africa and the Pyrenees.